Diversity and Dominance of Sea Urchins (Echinoidea) on Sambalagi Beach, Siompu Island, South Buton Regency - Maretik Maretik; Ramad Arya Fitra; Winardi Winardi (Jurnal Biologi Tropis, 2023)
Many species of sea urchins (Echinoidea) can be found in the waters of Sembalagi Beach, Siompu Island. However, the diversity of sea urchins (Echinoidea) on the coast has not been scientifically researched and published. This study aims to determine the types, hunting, poaching and dominance of sea urchins (Echinoidea) at Sambalagi Beach, Siompu Island, South Buton Regency. This study uses a quantitative descriptive method with observation techniques. There are three research stations, namely station I (rocky and seagrass substrate), station II (sandy and seagrass substrate), and station III (rocky and seagrass substrate). The data obtained were analyzed using the formulation of documents, documents, secrecy and Shannon-Winner domination. The results showed that there were 5 species of sea urchins (Echinoidea) which namely Diadema setosum, Echinothrix calamaris, Tripneustes gratilla, Echinometra mathaei and Salmacis sphaeroides. The species diversity index (H') for the three abnormalities was classified as moderate, namely station I (H' 1,34), station II (H' 1,18) and station III (H' 1,22). The highest relative abundance of Echinoidea was found in Tripneustes gratilla species at Station II (37,67%) which had a lot and the lowest relative decline index was found in Echinothrix calamaris and Echinometra mathaei at Station III (1,52%) less abundant. The highest evenness index is at station II (0,85) which is very even and the lowest is at station III (0,76) which is more evenly distributed. And the highest dominance index is at station II (0,32) with moderate dominance and the lowest dominance index is at station I (0,29) with low dominance.